Pengaruh Pendidikan Etika Terhadap Perpepsi Etis Mahasiswa Akuntansi: Studi Kasus Mahasiswa Angkatan 2023 - Fitria Intan Novianti; Nurul Aini; Tries Ellia Sandari (Journal of Economic and Business Advancement, 2025)
This study aims to analyze the effect of ethics education on the ethical perceptions of accounting students, with a case study of evening class students enrolled in the 2023 Accounting Study Program at Universitas 17 Agustus 1945 Surabaya. The background of this study stems from the increasing complexity of the business and accounting world, which requires accountants to not only be technically competent, but also have strong moral integrity. This study uses a quantitative survey method with a Likert scale questionnaire instrument. The data were analyzed using simple linear regression. The results show that ethics education has a positive and significant effect on students' ethical perceptions. The R Square value of 0.445 indicates that ethics education can explain 44.5% of the variation in ethical perceptions, while 55.5% is influenced by other factors outside the model. The regression coefficient of 0.427 and the significance value of 0.000 confirm that the better the ethics education students receive, the higher their ethical perceptions. These results support Kohlberg's moral development theory and are in line with previous research findings